Attitudes Towards Kurdish Language Among Kurdish Speakers in the West Part of Iran - Mohamad Javad Mehrifar; Hiwa Weisi; Kourosh Saberi (پژوهشنامه ادبیات کردی)
This study aims to investigate language attitudes among Kurdish speakers in the western part of Iran. A questionnaire was adopted for collecting the data. Then the final version of the questionnaire was distributed among people in target cities. 450 people participated in this part and answered the questionnaires voluntarily. The results of language attitude showed that the Kurdish language has a very high social status among people in Sene (Sanandaj) and Kermashan (Kermanshah) and a high social status among people in Ilam. Regarding its institutional support, people believe that the Kurdish language, though vital and widely used with a positive attitude among its native speakers, requires more institutional support. Regarding Kurdish vitality, the results showed that, unlike Sene, the Kurdish language may die out in the future in Kermanshah and Ilam. Finally, the results showed that there was no significant difference between males and females in their attitude to the Kurdish language in Kermashan and Sene, but there was an obviously significant difference between males' and females` language attitudes in Ilam. Finally, some suggestions for further research were proposed by the researcher.